Convalescent plasma therapy for the treatment of patients with COVID‐19: Assessment of methods available for antibody detection and their correlation with neutralising antibody levels. Issue 3 (17th December 2020) - Harvala, Heli; Robb, Matthew L.; Watkins, Nick; Ijaz, Samreen; Dicks, Steven; Patel, Monika; Supasa, Piyada; Wanwisa, Dejnirattisai; Liu, Chang; Mongkolsapaya, Juthathip; Bown, Abbie; Bailey, Daniel; et al.
Abstract: Introduction: The lack of approved specific therapeutic agents to treat coronavirus disease (COVID‐19) associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has led to the rapid implementation of convalescent plasma therapy (CPT) trials in many countries, including the United Kingdom. Effective CPT is likely to require high titres of neutralising antibody (nAb) in convalescent donations. Understanding the relationship between functional neutralising antibodies and antibody levels to specific SARS‐CoV‐2 proteins in scalable assays will be crucial for the success of a large‐scale collection. We assessed whether neutralising antibody titres correlated with reactivity in a range of enzyme‐linked immunosorbent assays (ELISA) targeting the spike (S) protein, the main target for human immune response. Methods: Blood samples were collected from 52 individuals with a previous laboratory‐confirmed SARS‐CoV‐2 infection. These were assayed for SARS‐CoV‐2 nAbs by microneutralisation and pseudo‐type assays and for antibodies by four different ELISAs. Receiver operating characteristic (ROC) analysis was used to further identify sensitivity and specificity of selected assays to identify samples containing high nAb levels. Results: All samples contained SARS‐CoV‐2 antibodies, whereas neutralising antibody titres of greater than 1:20 were detected in 43 samples (83% of those tested) and >1:100 in 22 samples (42%). The best correlations were observed with EUROimmun immunoglobulin G (IgG) reactivity (Spearman Rho correlation coefficient 0.88; p  < 0.001). Based on ROC analysis, EUROimmun would detect 60% of samples with titres of >1:100 with 100% specificity using a reactivity index of 9.1 (13/22). Discussion: Robust associations between nAb titres and reactivity in several ELISA‐based antibody tests demonstrate their possible utility for scaled‐up production of convalescent plasma containing potentially therapeutic levels of anti‐SARS‐CoV‐2 nAbs.